Corporate brand transgression and punishing the transgressor: moderation of religious orientation - Karaosmanoglu, Elif; Isiksal, Didem Gamze; Altinigne, Nesenur (Emerald Group Publishing Ltd, 2018)
Purpose - With the aim of developing a better understanding of why some consumers still excuse corporate brands that engage in transgressions, this study tests whether extrinsically religious people tolerate corporate brands more than intrinsically religious individuals at different transgression levels (severe and mild) and punish them less than the latter. Design/methodology/approach - This study adopts a 2 x 2 experimental design to manipulate corporate brand transgression levels (mild vs severe) and religiosity orientations (intrinsically religious vs extrinsically religious) on a convenience sample of 134 subjects who live in Turkey, a country where Islam shapes religious context. It uses a scenario technique and projective approach. Findings - While the main effect of corporate brand transgression on punishing behaviour does not appear in the analysis, religiosity's main effect on the latter does. Unexpectedly, extrinsically religious consumers punish corporate brand transgressors more than their intrinsically religious counterparts regardless of the transgression severity levels. Research limitation/implications - Although the study does not refer to any religion in particular, countries predominated by religions other than Islam may yield different consumer reactions. Future studies should focus on transgressions in such different settings. Practical implications - Corporate brand transgressors should immediately take up good causes to attract the attention of intrinsically religious consumers. Otherwise, for the sake of showing off, extrinsically religious people may punish the transgressor for its intentional mistakes, which may harm corporate brand associations. Originality/value - This study examines the link between religiosity and corporate branding. Unique in this way, it introduces religiosity as a valid contributor that can explain why some consumers do not punish corporate brand transgressors, especially in countries like Turkey where religiosity is intertwined with the developments in the liberal economy which led to the emergence of a new middle class.
Keywords: Corporate Brand; Religiosity; Brand Transgression; Punishing Behaviour; Religious Orientation; Social-Responsibility; Ethical Brand; Consumer; Forgiveness; Attributions; Management; Business; Globalization; Personality; Attitudes